EXPLOITATION OF WATER INDUSTRY AND PERSPECTIVES OF DEVELOPMENT - F. P. Gamidov (Литьë и металлургия)
The source of water supply of the plant is river water. The schema of the plant water supply is circulating, including the circulating cyclic processes of “pure ” water and circulating cyclic processes of muddy water. The water supply system is sprinkler.The river water is processed under the schema:Partial softening — at the facility of decarbonization;Softening - in sodium cation unit.The saline water after regeneration setting of chemical unit are processed at osmotic setting.The perspective of the water economy includes the modernization of the block of preliminary purification of the saline outflows and osmotic setting.